Exploring policy impacts for servicising in product-based markets: A generic agent-based model. (1st March 2017) - van der Veen, R.A.C.; Kisjes, K.H.; Nikolic, I.
Abstract: The shift to markets based on servicising, i.e. market-level transitions from product-based to service-based production and consumption patterns, may contribute to achieve absolute decoupling, i.e. the combined development of economic growth and environmental impact reduction. However, the potential of this contribution is largely unknown. In this paper a generic agent-based model of servicising is presented with which this potential can be explored further, taking into account decision making procedures of business and consumer agents, including market research, preferences, and willingness to pay. The details of the servicising model are presented, and the model's abilities are demonstrated through three case studies from different sectors: car and bike sharing, crop protection, and domestic water-saving systems. Absolute decoupling was found to occur in some of the policy scenarios, but results vary widely between cases. It is concluded that the model can be used to explore the impact of public policy on the uptake of servicising and on absolute decoupling in various sectors, and is therefore a useful support tool for policy makers who aim to promote servicising, as well as for researchers studying potential servicising impacts. Highlights: Servicising is a market transaction where the function of a product is sold. We present a generic agent-based model for exploring the potential of servicising. The functionalities of the model are demonstrated by three sector case examples. We conclude that the model is a valuable tool for studying servicising systems.